Small molecule Photoregulin3 prevents retinal degeneration in the Rho(P23H) mouse model of retinitis pigmentosa - Nakamura, Paul A (eLife, 2017)
Regulation of rod gene expression has emerged as a potential therapeutic strategy to treat retinal degenerative diseases like retinitis pigmentosa (RP). We previously reported on a small molecule modulator of the rod transcription factor Nr2e3, Photoregulin1 (PR1), that regulates the expression of photoreceptor-specific genes. Although PR1 slows the progression of retinal degeneration in models of RP in vitro, in vivo analyses were not possible with PR1. We now report a structurally unrelated compound, Photoregulin3 (PR3) that also inhibits rod photoreceptor gene expression, potentially though Nr2e3 modulation. To determine the effectiveness of PR3 as a potential therapy for RP, we treated Rho(P23H) mice with PR3 and assessed retinal structure and function. PR3-treated Rho(P23H) mice showed significant structural and functional photoreceptor rescue compared with vehicle-treated littermate control mice. These results provide further support that pharmacological modulation of rod gene expression provides a potential strategy for the treatment of RP.